Existence of the Baku'puli Tradition in Bonto Bulaeng Village, Bontotiro District, Bulukumba Regency - Yunus, Abdul Rahim; Rasyid, Suraya; Reskiani, Ezi (Pappaseng: International Journal of Islamic Literacy and Society, 2023)
This type of research is qualitative research using historical, anthropological and isociological research approaches. Sources of data in this research are village heads, traditional leaders, religious leaders, and several other community leaders. iThe data collection methods used are through observation, interviews, and documentation. Data processing and data analysis techniques are carried out by means of data reduction, data presentation, and verification or conclusion drawing.This research shows that the Baku'puli is an ittradition that originates from Inenek Imo, who has existed since the past, and still exists and has been carried out by the people of iBonto Bulaeng village until now as a form of respecting the heritage of ancestors. Ibaku'puli in iBonto Bulaeng village is done because of several factors and they think that ibaku'puli is a normal thing for some people. Because of its existence, it is the same as the other's submission. In iBonto iBulaeng village, every wedding uses my ibaku'puli which is regarded as an inheritance from an uncle who must be cared for, preserved, and protected as a form of respect for the culture that has been passed down from generation to generation.Regarding the implementation process, it has several stages, namely planning, preparation and implementation. This meaning of ibaku'puli i has a positive meaning in Desa Bonto Bulaeng's marriage, besides both brides want to be willing to establish a relationship in the household that is isakinah, imawaddah, iwarahma, it is hoped that they will remain united in the sense that it is hoped that there will be no disagreements that will result in the separation of his wife and his wife's separation I stay united and I can solve every problem in the households they raise, I also strengthen the husband and wife so that they remain harmonious, and I feel that I love each other.